Using messy play to promote self-discovery. (2nd June 2019) - Fillingham, Sarah
Abstract : Wonderfully natural and inclusive, sensory exploration leads to children's self-expression and wellbeing. Give them time to immerse themselves fully and observe how they go with the flow.